(untitled) (Emancipação, 2022)
This article analyzes the "Itaipu Binational Educational Project for the paraguayan right Margin", made possible during the construction period of the Itaipu Binational Hydroelectric Power Plant between 1974 and 1985m. On the right bank, Paraguay organized an ideological structure that was based on formal and non-formal education initiatives, made possible in the Housing Villages and Construction Site. Under the assumptions of historical-dialectical materialism, this research used theoretical, bibliographic, documentary and semi-structured interviews. It was concluded that, although the control and consensus-building strategies were similar to those used in the Brazilian left margin, in Paraguay there was greater participation of the public power in the provision of formal education, through agreements between the entity and the "Ministry of Education and Cult - MEC ".